Estimating sample size in experimental and non-experimental settings - Leiby, Benjamin E. (Henry Stewart Talks, 2022)
Testing hypotheses, Information needed for a sample size calculation, Null and alternative hypotheses, Type 1 and Type 2 errors, Risk difference, Power and sample size, Experimental vs. observational studies, Two-group comparisons